2020
DOI: 10.1002/edn3.134
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA is an effective tool to track recolonizing migratory fish following large‐scale dam removal

Abstract: Environmental DNA (eDNA) has emerged as a potentially powerful tool for use in conservation and resource management, including for tracking the recolonization dynamics of fish populations. We used eDNA to assess the effectiveness of dam removal to restore fish passage on the Elwha River in Washington State (USA). Using a suite of 11 species‐specific eDNA polymerase chain reaction (PCR) assays, we showed that most targeted anadromous species (five Pacific Salmon species and Pacific Lamprey) were able to pass up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 77 publications
(105 reference statements)
1
44
0
Order By: Relevance
“…Furthermore, the sensitivity test, including the LOD and LOQ determination, is required in the eDNA surveillance guidelines since many eDNA studies can detect low-abundance species within ecosystems. Previous species-specific eDNA studies in Pacific salmon do not contain adequate information regarding sensitivity tests, except that of Duda et al [ 73 ], who studied five Pacific salmon in the Columbia River (USA). Xia et al [ 74 ] reported that two of three eDNA studies consisted of newly developed markers, whereas only 88 of 165 studies determined the LOD of the marker.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the sensitivity test, including the LOD and LOQ determination, is required in the eDNA surveillance guidelines since many eDNA studies can detect low-abundance species within ecosystems. Previous species-specific eDNA studies in Pacific salmon do not contain adequate information regarding sensitivity tests, except that of Duda et al [ 73 ], who studied five Pacific salmon in the Columbia River (USA). Xia et al [ 74 ] reported that two of three eDNA studies consisted of newly developed markers, whereas only 88 of 165 studies determined the LOD of the marker.…”
Section: Discussionmentioning
confidence: 99%
“…To advance its use in this arena, Duda et al. (2021) used multiple species‐specific real‐time PCR assays to monitor over four years the fish distribution after a dam removal project in Elwha River, Washington, USA. Indigenous salmon species expanded their migrating area to the upstream side of removed dam sites whereas a non‐native Brook Trout has been suggested not to expand its range due to the dam removal.…”
Section: Impact and Restoration Assessmentmentioning
confidence: 99%
“…The removal of the two dams occurred between 2011 and 2014; full fish passage was restored at Elwha Dam in spring 2012 and at Glines Canyon Dam in fall 2014. Since dam removal, Chinook Salmon, steelhead, and Bull Trout have ascended to the headwaters of the Elwha River, Coho Salmon and Pink Salmon have passed the former Glines Canyon dam site, and Chum Salmon have passed the former Elwha Dam location (McMillan et al 2019; Duda et al 2020).…”
Section: Figurementioning
confidence: 99%